PENGEMBANGAN ARSITEKTUR INFORMASI DALAM MENUNJANG STRATEGI SI/TI MENGGUNAKAN PENDEKATAN BUSINESS SYSTEM PLANNING : STUDI KASUS YAYASAN CAHAYA SAKTI - Budi Supriyadi (Yayasan Akrab Pekanbaru, 2019)
In order to improve the quality of education and competitiveness, information systems provide the most important role in the business world. The development of information technology has caused role changes from the role of efficiency and effectiveness to become strategic roles. The preparation of the IS / IT planning strategy is a step taken by a company that wants a better corporate environment in the future. In the case of building a computer-based information system, a business plan and process can be defined so that the flow of information between business processes can be clearly described. Cahaya Sakti Foundation is an institute in the field of education. The writer uses the Business System Planning method which consists of four steps, namely defining Business Objectives, defining Business Processes, defining Data Classes and determining Information Architecture. The results of this research are information architecture where the aim is to integrate information needs, information components and supporting technologies, the final results of which are made of information architecture priorities.